The management of post-endodontic treatment using fiber-reinforced composite: a case report - Lambertus, R.; Suwartini, T.; Elline, E.; Prahasti, A.E.; Azman, Syuwari Azhar (CRC Press, 2024)
Post-endodontic treatment restoration with appropriate material is an essential factor. In this case, we choose a biomimetic approach. The dentin was then replaced with a biobased material, and the enamel was replaced with a composite restoration. In order to minimize the stress created in the hybrid layer, the biobased was additionally strengthened with polyethylene fiber at its base. A short fiber-reinforced composite resin that exhibits mechanical qualities similar to dentin was used to repair the dentin core. A 55-year-old female patient complained about a spontaneous throbbing pain in the upper left tooth. Upon completion of clinical assessment and test, tooth #24 was diagnosed with irreversible pulpitis. A non-surgical root canal procedure was carried out using an aseptic technique. Crown-down preparation and copious irrigation of 5.25% sodium hypochlorite were fol-lowed by root canal disinfection. The obturation was done using the warm vertical com-paction technique. Due to the amount of remaining dental hard tissue, the direct restoration using fiber-reinforced composite was chosen as the optimum treatment for the final restoration of tooth #24. Short fiber reinforced composite can be used as a treatment of choice for direct posterior restoration in post-endodontic treatment.